STIGMA TERHADAP ORANG DENGAN GANGGUAN JIWA (ODGJ) PADA MAHASISWA PROGRAM STUDI ILMU KEPERAWATAN STIKES JENDERAL ACHMAD YANI YOGYAKARTA - Dewi Retno Pamungkas; One May Linawati; Puji Sutarjo (MEDIA ILMU KESEHATAN, 2016)
Background: Stigma is a negative view of individuals that would have influences on how they feel about, and act upon others. Stigma towards people with mental health problems will negatively affect their recovery process. At a stage of their education, nursing students will meet with people with mental disorders. It is important to analyze their view towards people with mental disorders. Objective: This research aimed to gain an overview on nursing students’ stigma towards people with mental disorders at Stikes Jenderal Achmad Yani Yogyakarta. Methods: This study was descriptive quantitative with a cross sectional method and proportionate random sampling technique, involving 81 respondents. Data were obtained through a questionnaire. Students’ stigma was viewed from several aspects including education, gender, age and ethnicity. Stigma was assessed in three categories; low, moderate and high level of stigma. Result: Result showed that within the categories, the highest prevalence was in the moderate level of stigma (96.3% or 78 people), high level of stigma accounted for 3.7% (3 people), and there was not respondent with low level of stigma. Conclusion: The majority of nursing students at Stikes Jenderal Achmad Yani Yogyakarta had moderate level of stigma. Keywords: Stigma, mental disorder, nursing student